Aplication of Classification Proverty Society Status in Tegal District - Nur Halimatussa'diyah; Ginanjar Wiro Sasmito; Dyah Apriliani (Komputika : Jurnal Sistem Komputer, 2021)
Currently the Social Service has implemented a centralized computed population data collection, which has resulted in the social office unable to optimally process data on its citizens. The data processing still has several shortcomings that need to be overcome, namely in determining the value of the criteria for classifying the level of poverty of the population, which is carried out at the center. This study describes the classification of the poor as a breakthrough in producing information to the Social Service and the public about the level of poverty in Tegal Regency. This system is a website-based application designed for Social Service officers to process data on the poor. The method used in this application uses a weighting and ranking method. The result of this research is a website-based application that can classify poor residents, villages and sub-districts.